Sustainable Management Potential of a neglected Wild Olive (Olea cuspidata Wll.ex G. Don) in Sudurpaschim Province of Nepal - Joshi, Nabin Raj (International Journal of Atharva, 2026)
Background: Wild Olive (Olea cuspidata) is an ecologically and economically significant species in Nepal’s Sudurpaschim Province, yet its production potential remains understudied. Objectives: This study assessed Olive’s distribution, growing stock, and habitat suitability across Bajura and Bajhang districts to inform sustainable management strategies. Methods: This study employed a participatory resource mapping and Maximum Entropy (MaxEnt) modelling. Field data were collected from 62 concentric circular plots (500 m² each) across 12 Community Forests. Resource assessment followed the Non-Timber Forest Products Inventory Guideline and participatory inventory protocols. Results: Results showed high regeneration density (mean 17,472±100.2 seedlings ha⁻¹), with mature tree density averaging 133±12.5 ha⁻¹. Total growing stock reached 753.6 tonnes, with an annual allowable harvest of 678.5 tonnes. Optimal productivity occurred on north-facing slopes at 1,300–1,400 m elevation. MaxEnt modelling identified 636 hectares of community forest area with high suitability for Olive cultivation in Sudurpaschim province. Conclusion: The natural and wild Olive population holds a significant potential for sustainable management, value addition, processing and commercialization in Sudurpaschim Province. We recommend: (1) expanding cultivation in identified suitable areas, (2) developing processing infrastructure for value addition beyond crude oil, and (3) implementing certification schemes to enhance market access. These findings provide a blueprint for sustainable Olive management in the Himalayan region of Nepal. Novelty: This study provides a comprehensive assessment of Wild Olive (Olea cuspidata) in Sudurpaschim province, integrating MaxEnt habitat modelling with community-based phytosociology and value chain analysis to establish a scientific baseline for its sustainable commercialization and conservation.